Does scientific research change minds?: Linking criminology and public perceptions of policing - Boehme, Hunter M. (Criminology & public policy, 2024)
Research summary This study investigates the impact of scientific research findings on public views of policing topics. Specifically, we conducted an original survey experiment to determine whether research information treatments influence respondents’ views on the effectiveness of the police in reducing crime, defunding and refunding police budgets, and use of body-worn cameras. Our results indicated that presenting confirmatory research information had a significant positive impact on perceptions of police effectiveness in reducing crime and use of body-worn cameras compared to comparison groups. Conversely, presenting "negative" research information had a significant negative effect on these perceptions. Interestingly, neither positive nor negative research information treatments related to defunding versus refunding the police had a statistically significant impact on respondents compared to comparison groups, suggesting that research findings have limited effects on more ideologically complex policing topics. Policy implications Scientific research can effectively shape public perceptions of police effectiveness in reducing crime and the use of body-worn cameras, but it has limited effects on politically charged issues, such as defunding and refunding the police. To enhance the impact of evidence-based policing, we suggest that police administrators collaborate with researchers to evaluate new policies and disseminate these findings widely to the public. Additionally, researchers should strive to make their research more accessible to the general public, beyond academic journals, scientific conferences, and paywalls. We recommend using open-access platforms, social media, and other media outlets to disseminate unbiased, evidence-based research on policing that is digestible to the public.